Treatment outcomes of oral leukoplakia on the irradiated or nonirradiated mucosa among survivors of head and neck cancer in the papulation where practice of betel nut chewing and cigarette smoking are widespread - Shih-Wei Yang; Chien-Yu Lin; Yun-Shien Lee; Shih-Ming Huang (BMC Oral Health, 2024)
Abstract Background Radiotherapy (RT) has numerous effects on the oral mucosa, primarily genetic alterations and changes in the microenvironment. The characteristics of oral leukoplakia (OL) may differ between patients who have received previous head and neck cancer (HNC) treatment with radiation therapy and those who have not. Due to a lack of data on this scenario, we aimed to investigate the surgical outcomes of OL by comparing these two patient groups. Methods This retrospective cohort study enrolled a total of 224 OL lesions in 124 patients who underwent carbon dioxide laser (CO2 laser) surgery from July 2002 to Aug 2021. All patients had received previous treatments for HNC, with 59 patients undergoing only surgical approach, 65 patients undergoing RT, and 46 patients undergoing concurrent chemotherapy during RT. The analysis was performed on a per-lesion basis, not a per-capita basis. We investigated the associations of clinicopathological characteristics and treatment outcomes of OL lesions that developed from irradiated or nonirradiated oral mucosa. Results The median follow-up time was 5.87 years. Postoperative recurrence of OL occurred in 30 patients. Malignant transformation occurred in 17 patients with the incidence rate 4.19% annually and 13.7% cumulatively. The average time for OL transforming into squamous cell carcinoma was 3.27 ± 3.26 years (median 1.82, range 0.11 – 11.90). In univariate analysis, non-homogeneous morphology (P = 0.042), moderate to high-grade dysplasia (P = 0.041), and nonirradiated oral mucosa (P = 0.0047) were predictors for malignant transformation. However, in the Cox proportional hazard model, only nonirradiated oral mucosa remained an independent prognostic factor related to postoperative malignant transformation of OL (P = 0.031, HR 5.08, CI95 1.16 – 22.25). Conclusion In the population whose OL is strongly aetiologically linked to environmental carcinogens such as betel nut and tobacco, OL lesions that develop on previously irradiated oral mucosa have a lower risk for postoperative malignant transformation compared to those that develop on nonirradiated mucosa. This finding highlights the potential impacts of radiation on OL. Further research is needed to confirm this observation and elucidate the underlying mechanism.